“God at Work”: Engaging Central and Incompatible Institutional Logics through Elastic Hybridity - Gümüsay, Ali Aslan; Smets, Michael; Morris, Timothy (Academy of Management Journal, 2020)
Based on a 24-month ethnographic case study of the opening of the first Islamic bank in Germany, we make three contributions to the institutional theory literature. First, we outline “polysemy” and “polyphony” as mechanisms that dynamically engage conflicting logics through an organizational–individual interplay. Borrowing from paradox theory, we explain how hybrids can empower individuals to fluidly separate and integrate logics when neither structural compartmentalizing nor organizational blending is feasible because management cannot prescribe a specific balance of logics. Second, we explain the state of “elastic hybridity,” constituted through the recursive, multilevel relationship between polysemy and polyphony. Elastic hybrids maintain unity in diversity. They are capable of institutionally bending without organizationally breaking and thus enable individuals to practice more of their personal convictions at work while still experiencing a sense of shared organizational purpose. Third, we show how contested hybrids can be made to last. By dynamically making logics either less central or more compatible, elastic hybrids become less conflict prone and more resilient without permanently becoming more aligned or estranged.